Portugal - Lisi, M.; Freire, A. (The Palgrave handbook of radical left parties in Europe, 2023)
This chapter examines the evolution of the radical left in Portugal. While the first decade of the democratic period was marked by the anti-establishment position of the Portuguese Communist Party (PCP), which was the oldest party in Portugal and clearly the hegemonic force in the radical left camp, new developments characterised the last three decades. First, a new radical left party, the Left Bloc (BE), emerged in the late 1990s, increasingly competing with other left-wing parties and innovating the radical left agenda. Second, the power balance among left parties shifted during the beginning of the twenty-first century, with the slow and gradual decline of the PCP and growing fragmentation. Third, both parties have increased their institutional integration by collaborating with Socialist governments between 2015 and 2021.